Effects of exposure to direct and secondhand hookah and e-cigarette aerosols on ambient air quality and cardiopulmonary health in adults and children: protocol for a panel study. Issue 6 (24th June 2019) - Shearston, Jenni; Lee, Lily; Eazor, James; Meherally, Saher; Park, Su Hyun; Vilcassim, MJ Ruzmyn; Weitzman, Michael; Gordon, Terry
Abstract : Introduction: Use of alternative nicotine delivery systems, such as electronic cigarettes and hookahs, has increased dramatically in the USA, but limited research has been conducted on the secondhand effects of these products, especially in children. The objective of this study is to assess the cardiopulmonary effects of e-cigarette and hookah use in vaping and smoking adults, and in non-smoking/non-vaping adults and children exposed to secondhand particles and gases. Methods and analysis: This study uses a pre/post design, with four groups: two control groups (non-smoking/non-vaping and cigarette smoking) and two test groups (hookah smoking and e-cigarette vaping). Participants will be recruited by household, so that each home includes one smoking or vaping adult and one non-smoking/non-vaping adult and/or child (5–18 years). Non-smoking/non-vaping homes include an adult and child who do not smoke or vape and do not live with individuals who do. Air quality measures will be completed during a household smoking or vaping session (ambient air for non-smoking/non-vaping group), while cardiopulmonary measures and biological samples will be taken directly before and after the smoking/vaping session, and again 24 hours later, for all participants. Air quality measures include carbon monoxide, black carbon, particulate matter, trace elements, nicotine and carbonyls; cardiopulmonary measures include heart rate variability, blood pressure, pulmonary function and exhaled carbon monoxide; biological samples will assess cotinine, inflammatory cytokines and biomarkers in urine, saliva and nasal mucosa. Ethics and dissemination: This study was approved by the Institutional Review Board at New York University School of Medicine (s16-02226 and s17-01143). Special attention was given to the inclusion of children, who are likely significantly impacted by the use of these products at home, and thus should be included in research. Results of the study will be distributed at conferences, in peer-reviewed journals and to relevant public health authorities for use in developing policy.